Chemically synthesized ZnO-Bi2O3 (BZO) nanocomposites with tunable optical, photoluminescence and antibacterial characteristics. (September 2018) - Jan, Tariq; Azmat, Sohail; Wahid, Bareera; Adil, M.; Alawadhi, Hussain; Mansoor, Qaisar; Farooq, Zahid; Ilyas, S.Z.; Ahmad, Ishaq; Ismail, Muhammad
Abstract: This study unravels the soft chemical synthesis of Bi2 O3 /ZnO (BZO) nanocomposites having nano-cones like morphology with tunable optical and luminescent properties. The prepared BZO samples with varying Bi2 O3 concentrations have been characterized for structural, morphological, band gap energy, photoluminescence (PL) and antibacterial characteristics. Structural and morphological investigations revealed the separate single wurtzite phase of ZnO and monoclinic phase of Bi2 O3 without any undesired phases with dominant nano-cones like morphology. Optical and PL analysis have depicted the band gap widening, enhanced ultra-violet (UV) emission and decreased defects densities of BZO nanocomposites as compared to pristine ZnO nano-cones. Interestingly, a good correlation between defects and antibacterial activity of ZnO nanostructures has been found.